Importance of digital marketing in major sports events: On example of 2019 FIBA World Cup and AMG platform - Markov-Čikić Ivana; Veselinović Slaviša (College of Sports and Health, Belgrade, 2020)
Using the example of a major basketball sporting event such as the 2019 FIBA Basketball World Cup, we can clearly see how sport, as a particularly dynamic social field, has found its foothold in online media such as Adria Media Group platforms thanks to companies like Roda, which have become a part of the experience of major sports competitions, thus establishing a special relationship with consumers. The Roda commercial was present for over 16 days, 768 hours, or 3,987,456,000 seconds, a figure that is unimaginable on classic media such as nation-wide TV channels. In addition to the quantitative benefit mentioned above, it is important to note that the relations with Roda consumers, namely 2019 FIBA Basketball World Cup audience and AMG internet media audience have improved qualitatively because in the virtual market consumers become creators of the offer and from the very beginning direct the features of what they will buy.